2018
DOI: 10.1021/acs.jpca.8b07864
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Controlling Factors of the S0/S1 Minimum Energy Conical Intersection: A Theoretical Study

Abstract: The minimum energy conical intersection (MECI) geometries play an important role in photophysics and photochemistry. Although a number of MECI geometries can be identified using quantum chemical methods, their chemical interpretation remains unclear. In this study, a systematic analysis was performed on the MECIs between the singlet (S0) and lowest singlet excited (S1) states of organic molecules. The frozen orbital analysis (FZOA), which approximates the excited states with minimal main configurations, was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
3
6
0
Order By: Relevance
“…The SF‐TDDFTB and SF‐TDLCDFTB methods drastically reduced the computational cost with improved accuracy for MECI structures compared with SF‐TDDFT. Furthermore, as shown in our previous study obtained by SF‐TDDFT, the SF‐TDDFTB and SF‐TDLCDFTB calculations indicated the controlling factors, that is, K HL ≈ 0 at S 0 / S 1 MECIs.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The SF‐TDDFTB and SF‐TDLCDFTB methods drastically reduced the computational cost with improved accuracy for MECI structures compared with SF‐TDDFT. Furthermore, as shown in our previous study obtained by SF‐TDDFT, the SF‐TDDFTB and SF‐TDLCDFTB calculations indicated the controlling factors, that is, K HL ≈ 0 at S 0 / S 1 MECIs.…”
Section: Discussionsupporting
confidence: 77%
“…Finally, we verified the controlling factors of S 0 / S 1 MECI discovered in our previous studies at the SF‐TDDFTB and SF‐TDLCDFTB levels. Figure shows the HOMO−LUMO exchange integral, K HL , of Equation in hartree for S 0 EQ and S 0 / S 1 MECI structures of 29 molecules.…”
Section: Illustrative Applicationssupporting
confidence: 86%
See 2 more Smart Citations
“…Thus, non‐radiative decay pathways of AIEgens can be classified according to the deformation of their building blocks. The structures of the CIs of small molecules are classified into several types, which include ring puckering, torsions of double bonds, and ring openings . In fact, some mechanisms of AIEgens have been reported that are based on a coordinate including double bond torsion and ring puckering.…”
Section: Structure Of Typical Cis and Non‐radiative Decay Pathways Ofmentioning
confidence: 99%